Pengaruh Motivasi dan Kepuasan Kerja Terhadap Kinerja Karyawan PT Anugrahmitra Selaras - Seffani, Viska Rut; Sabariah, Etika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study was conducted to determine the effect of motivation and job satisfaction on employee performance at PT Anugrahmitra Selaras. Employee performance is an important factor in supporting productivity and achieving company goals. This research uses a quantitative approach with a survey method, through distributing questionnaires to 38 respondents who are company employees. The data analysis techniques used include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t test, F test, and coefficient of determination (R²) with the help of SPSS software version 25. The results showed that partially, motivation has no significant effect on employee performance, indicated by the t-count value of 1.449 t-table 2.028 and significance 0.156 0.05. Meanwhile, job satisfaction has a significant effect on employee performance with a t-count value of 3.351 t-table 2.028 and a significance of 0.02 0.05. Simultaneously, motivation and job satisfaction have a significant effect on performance, with an F-count value of 57.613 F-table 3.27 and a significance of 0.000 0.05. The coefficient of determination shows that motivation and job satisfaction contribute 76.7% to employee performance. Although motivation has no partial effect, but in combination with job satisfaction, both have an important role in improving employee performance.